Implementation of DASH (Dietary Approaches to Stop Hypertension) Education in Hypertension Patients with Knowledge Deficit Nursing Problems - Aryani, Dewi; Anggraini, Desy; Paizer, Dindi; Yamin, M. (STIKES Hesti Wira Sriwijaya, 2026)
Introduction: Hypertension is defined as an elevation in blood pressure beyond the normal limit, specifically exceeding 140/90 mmHg. The increase in blood pressure is attributed to indirect causes related to dietary habits and lifestyle, leading to a deficiency in knowledge. A knowledge deficit refers to a lack of cognitive information or non-adherence to recommended dietary and lifestyle modifications. Consequently, educational interventions are implemented to enhance understanding of appropriate lifestyle and dietary patterns. One non-pharmacological therapy that may be provided is education on the DASH (Dietary Approaches to Stop Hypertension) diet. This study aim was to provide an overview of DASH (Dietary Approaches to Stop Hypertension) education for hypertensive patients with the nursing diagnosis of knowledge deficit, by offering a clearer understanding of the importance of DASH (Dietary Approaches to Stop Hypertension) in hypertensive patients. Method: A descriptive design was used, which is a design intended to improve a knowledge deficit. Results: There was an effect on the knowledge deficit, resulting in an increase in knowledge and a change in blood pressure. This was evidenced by Client 1, who was able to answer 8 questions correctly on the questionnaire, with a percentage indicating 'Good,' while Client 2 was only able to answer 6 questions correctly, with a percentage indicating 'Fair,' due to factors such as age, education, and environment. Both clients appeared to understand the low-salt diet, and their blood pressure improved. Conclusion: Based on the results of the study involving two respondents, there was an effect on their knowledge deficit regarding DASH (Dietary Approaches to Stop Hypertension) as well as a change in their blood pressure.